Is Price-Volume Relationship Asymmetry? Intraday Evidence from Indian Stock Market - Paital, Rashmi Ranjan (Asian Journal of Empirical Research, 2015)
This paper examines the asymmetry in the price-volume relationship for 50 Indian stocks using high frequency 5-minute data set for the period July 2, 2012 to December 31, 2012. A dummy variable regression model is employed to check the asymmetric relationship. In sum, consistent with Moosa et al. (2003) we established an unusual asymmetry pattern in the return-volume relationship where this relationship is stronger when market goes up than when market goes down. Our findings do not support the proposition that “volume is relatively heavy in bull markets and light in bear markets”. A reason for this may be the Indian market is more sensitive to unfavorable news than favorable news.